2020
DOI: 10.3390/diagnostics10100854
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mutated ids Overexpression on IDS Enzyme Activity and Developmental Phenotypes in Zebrafish Embryos: A Valuable Index for Assessing Critical Point-Mutations Associated with Mucopolysaccharidosis Type II Occurrence in Humans

Abstract: Mucopolysaccharidosis type II (MPS II) is an X-linked disorder resulting from a deficiency in iduronate 2-sulfatase (IDS), which is reported to be caused by gene mutations in the iduronate 2-sulfatase (IDS) gene. Many IDS mutation sites have not yet had their causal relationship with MPS II characterized. We employed a gain-of-function strategy whereby we microinjected different mutated zebrafish ids (z-ids) mRNAs corresponded to human IDS gene into zebrafish embryos, and then measured their total IDS enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In another study, Bellesso et al utilized CRISPR/Cas9 technology to create a transgenic zebrafish line with a five-base-pair deletion in the z-ids gene, leading to a premature stop codon at amino acid 118 and a truncated form of z-IDS in cells. This loss of z-IDS function during early development decreased Fgf signaling and negatively impacted bone development at later stages [73]. Other notable PSGs exhibiting differentially expressed patterns in ovary tissue are methyltransferases (rnmt, dnmt1, trmt5) and it is well-known that oocyte growth is accompanied by dynamic epigenetic modifications [74].…”
Section: Plos Onementioning
confidence: 98%
“…In another study, Bellesso et al utilized CRISPR/Cas9 technology to create a transgenic zebrafish line with a five-base-pair deletion in the z-ids gene, leading to a premature stop codon at amino acid 118 and a truncated form of z-IDS in cells. This loss of z-IDS function during early development decreased Fgf signaling and negatively impacted bone development at later stages [73]. Other notable PSGs exhibiting differentially expressed patterns in ovary tissue are methyltransferases (rnmt, dnmt1, trmt5) and it is well-known that oocyte growth is accompanied by dynamic epigenetic modifications [74].…”
Section: Plos Onementioning
confidence: 98%
“…In addition, KO of ids in zebrafish has provided novel information about the role of early deregulation of the fibroblast growth factor signaling pathway in the occurrence of irreversible skeletal defects before glycosaminoglycans' accumulation [163]. With a different approach, human-mutated IDS mRNAs have been injected into zebrafish embryos for a rapid preliminary study about novel IDS point mutations associated with MPSII [164].…”
Section: Niemann-pick Diseasementioning
confidence: 99%
“…To solve this puzzling issue, the zebrafish is also a simple but cost-effective animal model that can serve as an in vivo screening platform. In this particular case, since the preparation of mRNAs for a gain-of-function study is simpler, more effective and economical than that of MO-injection for a loss-of-function study, Lin et al [ 88 ] demonstrated that overexpression of some uncharacterized mutant mRNA, which obviously leads to developmental defects, might also contain a potentially malignant mutation because the enzymatic activity of IDS encoded by this mutant mRNA is inactive. Consequently, the exogenous mutated IDS interrupts the enzymatic activity of endogenous IDS through the dominant negative effect, which, in turn, causes to occur developmental defects.…”
Section: Rare Disease and Screening For Potential Drugs Or Proteinsmentioning
confidence: 99%